2005
DOI: 10.1111/j.1600-051x.2005.00744.x
|View full text |Cite
|
Sign up to set email alerts
|

Bone height changes in individuals with periodontal disease: a 17‐year prospective longitudinal study

Abstract: Marginal bone level in this prospective study did reveal tooth groups at higher risk for progression of periodontal disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
1
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 34 publications
3
23
1
1
Order By: Relevance
“…These anatomical tooth characteristics may facilitate the retention of plaque and impair plaque removal and the access of instruments to distal sites. In contrast, some studies 2,4,24) reported greater bone loss at mesial sites.…”
Section: Resultsmentioning
confidence: 67%
See 2 more Smart Citations
“…These anatomical tooth characteristics may facilitate the retention of plaque and impair plaque removal and the access of instruments to distal sites. In contrast, some studies 2,4,24) reported greater bone loss at mesial sites.…”
Section: Resultsmentioning
confidence: 67%
“…Higher precipitation of calculus is usually observed in the upper molars and lower incisors, a fact favoring the accumulation of plaque and the consequent progression of periodontal disease in these two groups of teeth 33) . Some studies have demonstrated a higher bone loss rate in molars 2,4,23,24) , molars and incisors 34,46) or even a random distribution 43) . Lower bone loss was reported for canines 34) .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is estimated that 15 to 35% of the adult population in the industrialized countries suffers from this multifactorial disease [4]. Although microbes are required to initiate the pathological process, smoking is an important risk factor for the development of periodontitis; smoking also increases the severity of the disease [6,7]. In individuals with constitutional pro-inflammatory traits, the reaction to bacteria may lead to an excessive host response, resulting in systemic inflammatory reaction [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, smokers have a high predisposition of developing plaqueinduced periodontal diseases and consequently a higher prevalence [29,32,33]. Tobacco smoke is a major risk factor for periodontal disease because the oral cavity is the entryway for smoke into the airways and therefore naturally has the highest concentration of smoke components, especially in the gingival crevicular fluid (GCF) excreted from the gingival sulcus [93].…”
Section: Tobacco Smoke and Periodontal Diseasementioning
confidence: 99%